PERAN MU’TAZILAH DALAM MENAFSIRKAN AL QUR’AN - Khairunnas Jamal (Jurnal An-Nur, 2015)
Mu'tazila  is one of the theological schools in Islam which can be categorized as the rationalists of Islam . to determine Mu'tazilah rational pattern can be seen from the principal teachings derived from it, namely al - usul al - khamsah . This doctrine provides at- tawhid al - 'adlu , al - wa'du and al - wa'idu , al - manzilah Baina al - manzilataini nahyi commanding the good and forbidding the evil. in general epistemological interpretation Mu'tazila using the reason of human. Although the linguistic nuances dominant enough to use, but it has more of the linguistic studies which aim to interprate language meaning of the text that is not in accordance with reason . Mutazilah , in their view , it is always guided only on reason . This is done as a form of their opposition to the concepts of myth ( myth ) as opposed to the sense in which it has established its influence in the teachings of Islam.